An athermal measurement technique for long time constants traps characterization in GaN HEMT transistors. Issue 9 (August 2015) - Divay, A.; Masmoudi, M.; Latry, O.; Duperrier, C.; Temcamani, F.
Abstract: GaN High Electron Mobility Transistors (HEMTs) are very promising for high power switching and radiofrequency operation. However, the lack of reliability feedback is one of its major drawbacks. Trapping effect especially is one of the main performance limitations of such components. Many measurement techniques exist for trapping effects characterization, especially for short time constant traps (μs to several ms). However for longer time constants, self-heating may distort the measurements. This paper presents an electrical and athermal transient measurement method which has been developed to study the trapping and detrapping time constants of such components. It allows the extraction of slow transients without self-heating problems and is usable in long term electrical stress experiments. A simulation of this method with a simplified component's model and the measurements results are presented. With this technique, we investigated especially the long time constants (τ > 20 ms) over a range of temperature from 10 °C to 105 °C. We observed three thermally activated trap signatures on GaN devices with our method. Highlights: Electrical and athermal transient measurement method is developed to study trapping and detrapping. Simulation of electro-thermal HEMT with traps is done with electrical circuits of measure. Extraction of traps blind from the simulation is used to validate our method. Application is used on AlGaN/GaN 25 W power bar of 0.5 μm gates HEMT.